Advances and Setbacks of Educational Public Policies for Youth and Adult Education (EJA) in Brazil: The Use of Digital Technologies (Interdisciplinary Studies Journal, 2024)
This research aimed to analyze public policies for Youth and Adult Education (EJA) in the teaching and learning process with digital technologies. The study employed a qualitative-quantitative approach of an applied and descriptive nature. As a data collection tool, a semi-structured interview was conducted with 13 students, 8 teachers, and 2 members of the pedagogical team at the Dona Pérola Byington State School, located in Pérola, Paraná. For the analysis and interpretation of the results, content analysis and categorization by Bardin (2022) were used. The results showed both positive and negative aspects of the use of digital technologies in EJA and highlighted the need for digital inclusion for all, investment in continuous teacher training, and the promotion of public policies for this mode of education.
Keywords: Education; Public Policies; EJA; Digital Technologies